OPTIMASI PENEMPATAN DISTRIBUTION GENERATION PADA PENYULANG PUJON MENGGUNAKAN METODE PARTICLE SWARM OPTIMIZATION - Mas Ahmad Baihaqi; Rini Nur Hasanah; Hadi Suyono (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
This study proposes the use of Particle Swarm Optimization (PSO) algorithm to optimize the placement of Distributed Generation (DG) on the 20kV distribution system of Pujon feeder, which has 117 buses with the total distribution line length of 59.65 kilometers, with the aim to reduce power losses. In addition, PSO has also been used to determine the capacity of the DG. The JAYA algorithm is used as comparison. It has been proven that the proposed algorithm as well as the comparison algorithm succeeded in determining the optimum location and the capacity of DG to be installed